DNA Barcoding of Chinese species of the genus Eurydema Laporte, 1833 (Hemiptera: Pentatomidae) - Zhao, Wanqing; Zhao, Qing; Li, Min; Wei, Jiufeng; Zhang, Xianhong; Zhang, Hufang (Zootaxa, 2017)
The phenotype, as a significant identification character for the bug species Eurydema Laporte, 1833, possesses many variation patterns, making this species difficult to determine. In this context, DNA barcoding provides an efficient method for species identification. In our study, we used distance-based and tree-based methods to assess the effectiveness of COI gene as an additional taxonomic method. We examined COI sequences of 203 specimens collected in China. Intra- and interspecific genetic distances were calculated, and a phylogenetic tree was constructed using the neighbor-joining (NJ) method. The program TaxonDNA was used to calculate the distribution of distances and investigated the barcode gap. DNA barcodes revealed 100% (ABGD), 99.5% (TaxonDNA) and 97.5% (Barcode Index Numbers) successful identification rates. In the NJ tree, all taxonomic species showed monophyletic clusters that were separated from each other by large genetic distances (> 4.3%). Low divergence (< 0.6%) and non-monophyly clusters that included different phenotype variations were found in E. dominulus and E. oleracea. Compared with other Eurydema species, E. sp. had an average interspecific distance of 7.4% that was congeneric distance, and formed a distinct cluster among Eurydema tree clades. We also confirmed a new combination of Eurydema qinlingensis (Zheng, 1982) comb. nov. based on DNA barcoding and morphology data. Overall, our data showed that, despite the little barcode overlap between intra- and interspecific genetic distances, DNA barcoding is a useful and effective method for enhancing morphological data and resolving taxonomic problems.